PENGARUH SIZE, TANGIBILITY, PROFITABILITY TERHADAP STRUKTUR MODAL PADA PERUSAHAAN CONSUMERGOOD DI INDONESIA - Sjafii, H.; Akbar, dan Fajar Syaiful (Journal of Accounting and Strategic Finance, 2010)
There are some factors which influence the capital structure, such as: size company, growth level, and profitability. The goal of this research is to know what are the variable size company, growth level, and profitability to capital structure on consumer good company which have go public in Indonesia Stock Exchange. That factors can considered by company and can be used as information source by company to determine the capital structure. In this research using the sekunder data such as consumer good company data in Indonesia which is recorded in its financial reports along 2004 until 2008. The data analysis which have used is doubled linear regretion analysis. Meanwhile, to test the hypothesis which have been represent in research before, its used simultan test (F test) and partial test (T test). From the research result which is have been done, we can know that From result of calculation of hypothesis, obtained by result for the variable of Size measure Company have an effect on significant and positive to capital structure, for variable growth level do not have an effect on significant and positive to capital structure, for the variable of Profitability have an effect on negative and significant to capital structure. Keywords : Size Company, Growth Level, Profitability and Capital Structure.